Affirmative action and ethnic identity in black and indigenous brazilian children - França, Dalila Xavier de (2011)
Two studies of children aged between five and ten years old investigate the impact of affirmative action programmes on the ethnic identity of black and indigenous children in Brazil. The participants in the first study were children supported by affirmative action programmes: black Quilombola (n= 33) and indigenous (n= 32). Study two was carried out on black children (n= 77) not supported by affirmative action programmes. In the first study the children used nine different categories of skin colour to define themselves. The majority of the indigenous children defined themselves as “morena”, while black Quilombolas defined themselves as “preto” (dark). In the second study the children used six different colours, and dark colours were rarely used. Although the children in both studies liked belonging to their group, most, particularly the Quilombola children, would like to be whiter.